Kajian Fitokimia dan Analisis Kadar Fenolik Total Ekstrak Metanol Kulit Batang Merawan (Hopea mengarawan Miq.) - Pratibha, Muhammad Govindo Ibra; Rahmadanti, Diah Vio; Elviana, Dina; Ramadhan, Muhammad Farras; Pratama, Ngakan Putu Agung Dharma; Pramudia , Rista Anggi; Noviany, Noviany (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Dipterocarpaceae is a family of plants that has good wood quality and durability. Apart from that, wood for this family is known to contain the compound resveratrol which has bioactivity, such as anti-cancer and anti-inflammatory. Several genus and species of this family are threatened with extinction. Merawan (Hopea mengarawan Miq.) is one of extinct species from Dipterocarpaceae which according to several research contains secondary metabolite compounds. The objective of this research was to determine the content of secondary metabolite compounds and determine the total phenolic content of merawan. The maceration method was used to extract the stem bark of H. mengarawan Miq., then continued with phitochemical screening, and total phenolic content analysis. Phytochemical screening was carried out to identify secondary metabolite compounds contained in the methanol extract of H. mengarawan Miq. stem bark qualittatively. Determination of total phenolic content was carried out using the colorimetric method with Folin-Ciocalteu reagent and gallic acid as a comparison standard. The result of this study indicate that the methanol extract of stem bark of H. mengarawan Miq. contains secondary metabolite compounds, such as saponins, steroids, tannins, alkaloids, flavonoids, and phenolic with the total phenolic content of 13,518±0,228 mg GAE/g.